Effects of tofacitinib on nucleic acid metabolism in human articular chondrocytes. Issue 4 (July 2015) - Koizumi, Hideki; Arito, Mitsumi; Endo, Wataru; Kurokawa, Manae S.; Okamoto, Kazuki; Omoteyama, Kazuki; Suematsu, Naoya; Beppu, Moroe; Kato, Tomohiro
Abstract Objective. In our previous screening of chondrocyte protein profiles, the amount of adenosine monophosphate deaminase (AMPD) 2 was found to be decreased by tofacitinib. Extending the study, here we confirmed the decrease of AMPD2 by tofacitinib and further investigated effects of tofacitinib on purine nucleotide metabolism. Methods. Human articular chondrocytes and a chondrosarcoma cell line: OUMS-27 were stimulated with tofacitinib. Then the levels of AMPD2 and its related enzymes were investigated by Western blot. The levels of AMP and adenosine were assessed by mass spectrometry. Results. We confirmed the significant decrease of AMPD2 by tofacitinib in chondrocytes (p = 0.025). The levels of adenosine kinase and 5'-nucleotidase were decreased in chondrocytes, although they did not meet statistical significance (p = 0.067 and p = 0.074, respectively). The results from OUMS-27 were similar to those from the chondrocytes. The cellular adenosine levels were significantly decreased by tofacitinib in OUMS-27 (p = 0.014). The cellular AMP levels were increased, although they did not meet statistical significance in OUMS-27 (p = 0.066). Conclusion. Our data indicate that tofacitinib increases the cellular levels of adenosine, which is known to have anti-inflammatory activity, through the downregulation of AMPD2. This would be a novel functional aspect of tofacitinib.